Women Organisations as Drivers of Grassroots Political and Social Participation in Niger State - Lakan, M. J.; Lemu, H. I.; Abdullahi, S.; Umar, Y. (Journal of Research in Adult and Continuing Education, 2025)
This study investigates the role of women organisations in driving grassroots political and social participation in Niger State, Nigeria. While women groups have become central to civic engagement, their contributions at the local level remain under-documented. A descriptive survey design was employed, integrating both quantitative and qualitative approaches. The population comprised leaders and members of women organisations, community development officers, and selected political office holders. Using multistage and stratified sampling, 600 respondents were drawn from six purposively selected local government areas across the three geopolitical zones of the state, ensuring representation from both rural and urban communities. Data were collected through structured questionnaires, key informant interviews, and focus group discussions. Expert validation confirmed the suitability of the instruments, and reliability was established with a Cronbach’s Alpha coefficient of 0.82. Quantitative data were analysed with descriptive statistics such as means and percentages, while qualitative data underwent thematic analysis. Findings show that women organisations significantly enhance voter education, encourage female candidacy, and facilitate grassroots political dialogues. They also promote social development by spearheading vocational training, maternal health advocacy, poverty alleviation, and environmental sanitation. However, challenges including inadequate funding, cultural restrictions, weak institutional support, and limited media visibility hinder their broader impact. The study concludes that women organisations are indispensable to grassroots democracy and community development in Niger State. It recommended that there is need to increased public funding, the creation of gender units in local governments, stronger leadership capacity building, and strategic collaboration with male allies and traditional institutions to amplify their effectiveness.